Historiography of politics of the Soviet state 1929–1939 regarding the Old Believers - Latyshau, Kiryl A. (Journal of the Belarusian State University. History, 2021)
Based on the analysis of the post-Soviet Russian scientific historiography, the system-forming directions of studying the confessional Soviet policy of the period 1929–1939 are determined, due to significant changes in confessional policy from the reorganisation of the Anti-Religious Commission under the Central Committee of the All-Union Communist Party (b) (1929), the adoption of the resolution «On Religious Associations» (1929) and other transformations till the start of the Second World War, due to the expansion of the territory of the Soviet Union, where the previous stages of anti-religious policy had been not carried out. In view of the need to expand the field of historiographical sources, we carried out a thematic and synthesis analyses of the regional Russian studies of the history of the Old Believers, that do not have significant connections at the interregional level, despite the significant quantitative and qualitative growth of the thematic studies in the post-Soviet period. We have identified three general directions of historical development: the closure of Old Believer churches, repressions against clergymen, anti-religious agitation. The general tendencies within the framework of individual research subjects the most important problems and approaches to them are identified and characterised. The reasons are formulated allowing to consider the anti-religious policy towards the Old Believers as an independent phenomenon.